2019
DOI: 10.1016/j.canlet.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Towards the first targeted therapy for triple-negative breast cancer: Repositioning of clofazimine as a chemotherapy-compatible selective Wnt pathway inhibitor

Abstract: Wnt signaling is overactivated in triple-negative breast cancer (TNBC) and several other cancers, and its suppression emerges as an effective anticancer treatment. However, no drugs targeting the Wnt pathway exist on the market nor in advanced clinical trials. Here we provide a comprehensive body of preclinical evidence that an anti-leprotic drug clofazimine is effective against TNBC. Clofazimine specifically inhibits canonical Wnt signaling in a panel of TNBC cells in vitro. In several mouse xenograft models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 66 publications
4
36
0
Order By: Relevance
“…CWP232228, a small molecule that selectively inhibits Wnt pathway signaling by blocking nuclear β-catenin interaction with T-cell factor, reduced tumor growth in TNBC xenograft models and had a strong effect against chemoresistant breast CSC both in vitro and in vivo [84]. A repurposed drug clofazimine demonstrated efficacy in reducing the proliferation of TNBC cells and tumor growth in xenograft models [85]. Clofazimine negatively impacted β-catenin accumulation in the cytosol, thus downregulating the pathway and reducing the expression of ABC transporters [85].…”
Section: Tnbc Chemoresistancementioning
confidence: 99%
“…CWP232228, a small molecule that selectively inhibits Wnt pathway signaling by blocking nuclear β-catenin interaction with T-cell factor, reduced tumor growth in TNBC xenograft models and had a strong effect against chemoresistant breast CSC both in vitro and in vivo [84]. A repurposed drug clofazimine demonstrated efficacy in reducing the proliferation of TNBC cells and tumor growth in xenograft models [85]. Clofazimine negatively impacted β-catenin accumulation in the cytosol, thus downregulating the pathway and reducing the expression of ABC transporters [85].…”
Section: Tnbc Chemoresistancementioning
confidence: 99%
“…Chemotherapy is the current standard of care for advanced TNBC despite limited efficacy and poor survival outcomes [13]. Different targeted treatments for TNBC are under pre-clinical or clinical development [13,14]. Even though most breast cancer patients are diagnosed early enough to be successfully treated with surgery, chemotherapy, radiotherapy, or a combination thereof [8], nearly 30% of women that are initially diagnosed with early-stage disease will eventually develop a metastatic disease [7], which ultimately leads to patient death.…”
Section: Basal-likementioning
confidence: 99%
“…This drug inhibited Wnt/β-catenin signaling efficiently, suppressed growth tumor, and induced apoptosis. Moreover, the authors observed that clofazimine was compatible with doxorubicin and that this combination demonstrated an additive effect both in vitro and in vivo (47).…”
Section: Drugs That Target Wnt/β-catenin Signalingmentioning
confidence: 98%